2008
DOI: 10.1227/01.neu.0000316019.28421.95
|View full text |Cite
|
Sign up to set email alerts
|

Identification of A2b5+cd133− Tumor-Initiating Cells in Adult Human Gliomas

Abstract: Together, these results demonstrate that human gliomas contain multiple populations of cells with the capacity to form tumors and specifically identify a population of tumorigenic A2B5+ cells that are phenotypically distinct from CD133+ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
269
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(291 citation statements)
references
References 25 publications
19
269
3
Order By: Relevance
“…It is intriguing that hypoxia might expand cells with enhanced infiltrative property. A2B5, a cell surface ganglioside glial progenitor marker, is a putative CSC marker also associated with tumor recapitulation in xenografts (Ogden et al, 2008). Finally, high levels of CD24 expression have been used to identify transit-amplifying cells as well as differentiated neurons, and CD24 is required for the terminal differentiation of neuronal progenitors (Nieoullon et al, 2005;Panchision et al, 2007).…”
Section: Growth Of Cscs In Hypoxiamentioning
confidence: 99%
“…It is intriguing that hypoxia might expand cells with enhanced infiltrative property. A2B5, a cell surface ganglioside glial progenitor marker, is a putative CSC marker also associated with tumor recapitulation in xenografts (Ogden et al, 2008). Finally, high levels of CD24 expression have been used to identify transit-amplifying cells as well as differentiated neurons, and CD24 is required for the terminal differentiation of neuronal progenitors (Nieoullon et al, 2005;Panchision et al, 2007).…”
Section: Growth Of Cscs In Hypoxiamentioning
confidence: 99%
“…Several molecules, including CD133 (Singh et al, 2003(Singh et al, , 2004, CD15 (Read et al, 2009;Son et al, 2009;Ward et al, 2009), A2B5 (Ogden et al, 2008;Tchoghandjian et al, 2010) and L1CAM (Bao et al, 2008), have been identified on cell surface of GSCs (Fig. 1B, 3A).…”
Section: Specific Cell Surface Molecules In Glioblastoma Stem Cellsmentioning
confidence: 99%
“…But whether CD15 can be used as a target for GSCs is not clear because the function of CD15 in normal stem cells and cancer stem cells remains poorly understood, and CD15 is a carbohydrate antigen expressed by normal neural and progenitor cells (Capela and Temple, 2002) rather than a distinct protein target. Other surface markers such as A2B5 have been used for the enrichment of GSC population (Ogden et al, 2008;Tchoghandjian et al, 2009), but further investigations are needed to determine whether this surface marker can be used for targeting GSCs in GBMs.…”
Section: Specific Cell Surface Molecules In Glioblastoma Stem Cellsmentioning
confidence: 99%
“…Recent work on GBM has focused highly on the small fraction of tumor cells with stem cell characteristics that are thought to initiate and maintain tumor growth (Hemmati et al 2003;Singh et al 2003;Galli et al 2004;Singh et al 2004). Several markers identifying a glioma stem cell population have been proposed, including CD133, Nestin (Singh et al 2003), and A2B5 (Ogden et al 2008). HIF-2α was recently shown to be expressed at high levels in CD133 + glioma stem cells grown in vitro (McCord et al 2009), and to co-localize with stem cell markers in tumor specimens ), suggesting that HIF-2α is an independent marker for glioma stem cells.…”
Section: Non-small Cell Lung Carcinoma Hif Protein Expression Is Virmentioning
confidence: 99%